A search for transit timing variations and orbital decay in WASP-46b - Petrucci, Romina Paola (2018)
We present 12 new transit observations of the exoplanet WASP-46b obtained with the 1.54-m telescope at Estación Astrofı́sica de Bosque Alegre (EABA, Argentina) and the 0.40-m Horacio Ghielmetti and 2.15-m Jorge Sahade telescopes at Complejo Astronómico El Leoncito (CASLEO, Argentina). We analyse them together with 37 light curves from the literature to re-determine the physical parameters and search for additional planets via transit timing variations (TTVs). We consider the 31 transits with uncertainties in their mid-transit times (e_T0) < 1 min, to perform the first homogeneous study of TTVs for the system, finding a dispersion of σ = 1.66 min over a 6 yr baseline. Since no periodic variations are found, ourinterpretation for this relatively high value of σ is that the stellar activity could be affecting the measured mid-transit times. This value of dispersion allows us to rule out the presence of additional bodies with masses larger than 2.3, 4.6, 7 and 9.3 M⊕ at the first-order mean-motion resonances 2:1, 3:2, 4:3 and 5:4 with the transiting planet, respectively. Despite the 6 yr baseline and a typical light-curve precision of 2 × 10^(−3), we find that we cannot significantly demonstrate a slow decrease of the orbital period of WASP-46b. We place a lower limit ofQ* > 7 × 10^(3) on the tidal quality factor and determine that an additional 6 yr baseline is required to rule out Q* < 10^(5).